Updating zoology content in school textbooks: from junior high to elementary education - Willian Mirapalheta Molina; Lavínia Schwantes; Bruna Silveira de Freitas; Pedro Leal de Souza; Jonathan Cardoso Farias Farias (Amazônia, 2025)
Textbooks are fundamental resources in basic education. They reflect power relations and worldviews that shape students’ learning. In this study, we aimed to analyze the updating of zoology content in Natural History textbooks (1920s), Science (2013), and Natural Sciences (2018 and 2019). Through this historical investigation, we sought to identify changes and continuities in pedagogical approaches, avoiding value judgments and anachronisms. We acknowledge that each textbook is situated within a specific historical and social context. Our findings indicate that the zoological content in the analyzed textbooks is almost exclusively anchored in taxonomy. This emphasis may limit the understanding of animals to nomenclature and classification, overlooking their environmental interactions as well as ethical and social perspectives. We conclude that it is crucial to adopt an approach that fosters a broader understanding of zoology, reflecting what we consider significant for students’ relationships with other animals.